Improving Understanding In Class Fiqih Subjects IV with Method Discussion in MIS Mambaul Ulum - Isnawati, Titin; Saifullah; Zuroidah, Ninik; Tohari, Ilham (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This research aims to examine the application of the discussion method for overcome problems in the classroom related to students' low understanding of Fiqh subjects for class IV students at MIS Mambaul Ulum, Regency Lacquer. So far, teachers have used the lecture method on the eyes these lessons and tends to make learning less active and teacher-centered. This results in students not getting it good learning experience and has an impact on low understanding they. To overcome this problem, researchers took a method discussion learning to improve understanding of subjects FIQIH. This research is Classroom Action Research with a model Kemmis and Mc Taggart which consists of 3 cycles. Data collection technique What researchers use are observation, interviews, tests and documentation. Results research from cycles I and II can be concluded as follows: (1) Application learning using the discussion method went well through improvement at the reflection stage in each cycle. This is proven by the increase student learning outcomes from cycle I to cycle II. In cycle I the results of understanding Students in cycle I obtained an average score of 68 incomplete categories. In cycle II, students' learning outcomes experienced an increase in the average score into 81 complete categories.